Safety, Tolerability, and Pharmacokinetics of Remdesivir, An Antiviral for Treatment of COVID‐19, in Healthy Subjects - Humeniuk, Rita; Mathias, Anita; Cao, Huyen; Osinusi, Anu; Shen, Gong; Chng, Estelle; Ling, John; Vu, Amanda; German, Polina (Clinical and translational science, 2020)
Remdesivir (RDV), a single diastereomeric monophosphoramidate prodrug that inhibits viral RNA polymerases, has potent in vitro antiviral activity against severe acute respiratory syndrome‐coronavirus 2 (SARS‐CoV‐2). RDV received the US Food and Drug Administration (FDA)’s emergency use authorization in the United States and approval in Japan for treatment of patients with severe coronavirus disease 2019 (COVID‐19). This report describes two phase I studies that evaluated the safety and pharmacokinetics (PKs) of single escalating and multiple i.v. doses of RDV (solution or lyophilized formulation) in healthy subjects. Lyophilized formulation was evaluated for potential future use in clinical trials due to its storage stability in resource‐limited settings. All adverse events were grade 1 or 2 in severity. Overall, RDV exhibited a linear profile following single‐dose i.v. administration over 2 hours of RDV solution formulation across the dose range of 3–225 mg. Both lyophilized and solution formulations provided comparable PK parameters. High intracellular concentrations of the active triphosphate (~ 220‐fold to 370‐fold higher than the in vitro half‐maximal effective concentration against SARS‐CoV‐2 clinical isolate) were achieved following infusion of 75 mg or 150 mg lyophilized formulation over 30 minutes or 2 hours. Following multiple‐doses of RDV 150 mg once daily for 7 or 14 days, RDV exhibited a PK profile similar to single‐dose administration. Metabolite GS‐441524 accumulated ~ 1.9‐fold after daily dosing. Overall, RDV exhibited favorable safety and PK profiles that supported once‐daily dosing.